Prevalence of mobile usage among university students: a case study of International Islamic University Malaysia - Qadri, Mehran; Abubaka, Yusree; Ibrahim, Jamaludin (IJSRP.org, 2015)
Mobile usage among university students is an essential part of a student’s life nowadays. Students accomplish various tasks on a daily basis using mobile devices. Contacting classmates, professors and friends is done regularly via mobile devices. However the way these tasks are accomplished has changed dramatically in the past five or six years. New mobile technologies such as high speed mobile internet (3G, 4G LTE), the introduction of smartphones backed by hundreds of thousands of mobile applications, have launched a new dimension to how students now use mobile technology. This survey will investigate the current trends of students’ mobile usage at the International Islamic University Malaysia. The survey will also compare these current trends with the past trends of university students’ mobile usage and discuss how these trends have changed. Finally, this survey will try to predict the future trends of mobile usage among university students at IIUM. A total of 40 questionnaires were distributed among students from various faculties. The questionnaire consisted of 18 questions split into two parts. Part 1 asked a couple of demographic questions. Part 2 measured the prevalence of mobile usage among the students. The results were analyzed and some conclusions were drawn. Some predictions were made about the future of mobile usage among university students.